Mechanisms of sex hormones in autoimmunity: focus on EAE - Ninaad Lasrado; Ting Jia; Chandirasegaran Massilamany; Rodrigo Franco; Zsolt Illes; Jay Reddy (Biology of Sex Differences, 2020)
Abstract Sex-related differences in the occurrence of autoimmune diseases is well documented, with females showing a greater propensity to develop these diseases than their male counterparts. Sex hormones, namely dihydrotestosterone and estrogens, have been shown to ameliorate the severity of inflammatory diseases. Immunologically, the beneficial effects of sex hormones have been ascribed to the suppression of effector lymphocyte responses accompanied by immune deviation from pro-inflammatory to anti-inflammatory cytokine production. In this review, we present our view of the mechanisms of sex hormones that contribute to their ability to suppress autoimmune responses with an emphasis on the pathogenesis of experimental autoimmune encephalomyelitis.